Race and performance after repetition - Colbert, Soyica Diggs, 1979-; Jones, Douglas A.; Vogel, Shane (Duke University Press, 2020)
"RACE AND PERFORMANCE AFTER REPETITION considers the various and complex temporalities of both performance and racial aesthetics. Editors Soyica Colbert, Douglas Jones, and Shane Vogel note that performance studies has long relied on a dominant concept of repetition. Taking inspiration from José Esteban Muñoz's work, the contributors to the collection argue that minoritarian life schedules and cultural productions alike actually exist in multiple temporalities. They take up the work of non-white artists and communities to center temporal tropes that relate to, but diverge from, repetition. Theorizing raced time through time signatures, this collection proposes a spectrum of coexisting racial temporalities. The contributions are divided into three parts, the first of which focuses on the temporality of race, history, and form in theater. For example, Patricia Herrera explores the loop in UNIVERSES' production Party People (2016), which samples speeches by the Black Panthers and Young Lords, as a sonic treatise of futurity. The chapters in Part II consider how gesture, dance, and movement can recalibrate the temporal narratives of racial subjection. For example, Tina Post considers narrative tropes of animal and mechanical movement in reporters' stories about boxer Joe Louis. Katherine Zien examines Cuisine et Confessions (2014)- a "cultural circus" in which performers cook onstage, talk about their intimate lives, and perform high-risk circus feats-to show that arcs of time and space allow minoritarian identities to emerge in performance on their own time. The chapters in the Part III each take up what music misleadingly names the rest-an interval or pause of silence. The authors in this section consider the agency, critique, and hope that percolate in such stasis, such as Jisha Menon's focus in Chapter 10 on feminist natality as an alternative to punitive measures of liberal legality in Indian sexual violence cases"--